How are the Learning Organization Traits of Venezuelan Higher Education Institutions Compare with Other Organizations Worldwide - Nelly Fernández de Morgado; Guillermo Álvarez (Universidad Autónoma de Madrid, 2018)
The present article compares the learning organization traits of two Venezuelan higher education institutions with other organizations world wide. The purpose is, on the one hand, to envision Venezuelan universities within a global context. And, on the other hand, to ponder the nature and magnitude of the changes that Venezuelan universities have to plan in other to be effective organizations.  Fernández (2007) describes the learning organization traits of two institutions of higher education in Venezuela, one public and one private, according to the perception of two intermediate management teams. This article compares that data with Watkins and Marsick (1997-1999) data base which has world wide information about organizational learning. The results of this comparison showed that the public institution did not differ significantly in three out of seven imperatives, but it is significantly below the data base in the other four. The private institution, on the other hand, has significantly higher values than the data base, in all of the imperatives.  The relevance of this study underlies in the fact that it suggests strategic areas in which the Venezuelan higher education institutions should probably plan to invest, in research and development, in order to be effective. The scope of the application of the present study's results is limited due to the fact that only a small number of people took part in the survey.